2013
DOI: 10.1159/000353440
|View full text |Cite
|
Sign up to set email alerts
|

Review of Emotion Recognition in Stroke Patients

Abstract: Objective: Patients suffering from stroke have a diminished ability to recognize emotions. This paper presents a review of neuropsychological studies that investigated the basic emotion processing deficits involved in individuals with interhemispheric brain (right, left) damage and normal controls, including processing mode (perception) and communication channels (facial, prosodic-intonational, lexical-verbal). Methods: An electronic search was conducted using specific keywords for studies investigating emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 177 publications
5
64
4
Order By: Relevance
“…A larger sample would be necessary to test for laterality effects in patients with insular damage more specifically, but these data suggest that the left insular injury may be associated with more severe impairments in social information processing. These results are discordant with the right-hemisphere hypothesis of emotion processing (Sedda et al, 2013;Yuvaraj et al, 2013), and with the results from a lesionmapping study involving over 100 patients, which showed that lesions in the right somatosensory-related cortices, including the insula, were associated with impaired recognition of emotions from human facial expressions (Adolphs et al, 2000). Nevertheless, a more recent, large voxel-based lesion-symptom mapping found that only the left insula was significantly involved in facial emotion recognition impairment following penetrating brain injury (Dal Monte et al, 2013).…”
Section: Discussioncontrasting
confidence: 43%
“…A larger sample would be necessary to test for laterality effects in patients with insular damage more specifically, but these data suggest that the left insular injury may be associated with more severe impairments in social information processing. These results are discordant with the right-hemisphere hypothesis of emotion processing (Sedda et al, 2013;Yuvaraj et al, 2013), and with the results from a lesionmapping study involving over 100 patients, which showed that lesions in the right somatosensory-related cortices, including the insula, were associated with impaired recognition of emotions from human facial expressions (Adolphs et al, 2000). Nevertheless, a more recent, large voxel-based lesion-symptom mapping found that only the left insula was significantly involved in facial emotion recognition impairment following penetrating brain injury (Dal Monte et al, 2013).…”
Section: Discussioncontrasting
confidence: 43%
“…This finding indicate that stronger right than left-hemispheric degeneration in PD may lead to impairments in emotion recognition. This results are in line with Garrido-Vasquez (Garrido-Vásquez et al 2013;Ventura et al 2012), who reported that LPD had more difficulty with emotion processing since there is evidence that the processing of emotional information is righthemisphere dominant (Yuvaraj et al 2013). Furthermore, the right hemisphere is thought to be involved in social awareness and the in the recognition of salient social cues (Ventura et al 2012).…”
Section: Resultssupporting
confidence: 81%
“…To orient the reader, focussed literature on the neurology of EP has suggested a number of key themes, namely that EP as a whole may be right-lateralised (J. C. Borod, Bloom, Brickman, Nakhutina, & Curko, 2002;Yuvaraj, Murugappan, Norlinah, Sundaraj, & Khairiyah, 2013), or that it may be lateralised according to valence with the right hemisphere being responsible for the perception of negative emotions and the left hemisphere being important for perceiving positive emotions (Ahern & Schwartz, 1979;Davidson, Mednick, Moss, Saron, & Schaffer, 1987). Both the right-hemisphere and valence hypotheses have, however, been contested (Abbott, Wijeratne, Hughes, Perre, & Lindell, 2014).…”
Section: Lesion Study Data On the Relationship Between Emotion Percepmentioning
confidence: 99%